ATTRACTED RESOURCES OF A COMMERCIAL BANK - O. Belyaeva (Вестник Северо-Кавказского федерального университета, 2022)
The relevance of this work is confirmed by the fact that in the modern Russian economy there is a tendency towards a decrease in liquidity, as well as a continuing crisis in the financial sector, in connection with which the competition for inexpensive attracted resources is increasing annually. To expand the bank's resource base, it is important to use a competent customer attraction policy, which will be based on n cont aintaining the required level of diversiication, ensuring the ability to ind funds from any source and olling the balance of assets with liabilities in terms of maturity, volume and interest rates.